Mitochondrial DNA control region sequences may differentiate Yanbian Koreans in China from other Asian populations - Xiao-na Li; Ji-long Zheng; Jun Yao; Yue Dong; Zhang-sen Shi; Bao-jie Wang (Taylor & Francis Group, 2017)
Background: Sequence polymorphisms of mitochondrial DNA (mtDNA) are valuable in forensic medicine and anthropological genetics. Aim: This study investigated the mtDNA control region sequences in 295 unrelated individuals living in the Yanbian Korean Autonomous Prefecture in the People's Republic of China. Subjects and methods: DNA was extracted from blood stained filter papers. Hypervariable regions of the mtDNA control region (HVI and HVII) were amplified and sequenced. The resulting sequences were aligned and compared with the revised Cambridge reference sequence (rCRS). Results: A total of 182 variations were confirmed. Population comparison showed the significant difference between Yanbian Korean and other included populations. Conclusion: These results provide useful data for human genetic studies and forensic examinations and demonstrate that the Yanbian Korean population is an endogamous Northeast Asian group.